Pengaruh Suplementasi Oral Vitamin D terhadap Penurunan Keparahan Gejala pada Urtikaria Spontan Kronis: Sebuah Tinjauan Naratif - Nurul Izzah; Gardenia Akhyar; Abdiana Abdiana (Fakultas Kedokteran, Universitas Andalas, 2021)
Background: Chronic Spontaneous Urticaria (CSU) is a common allergic skin disease. The etiopathogenesis remains unclear. Recommended therapy is only aimed to reduce and control the symptoms. Vitamin D is a potential immunomodulator that can be used as an alternative therapy of urticaria. Objective: This literature study aims to explores various original research literature about the effect of vitamin D in CSU and the mechanism behind that. Methods: Narrative review of the literature that searched through three databases with determined keywords, then selected based on inclusion and exclusion criteria. Results: There are six literatures with 621 CSU cases. Conclusion: Vitamin D supplementation can reduce the severity of the symptom in CSU patient